Evaluation of Lignin Removal from Recycled Paper Mill Effluent (RPME) under Different Start-Up’s Steady State Conditions of Modified Anaerobic Inclining-Baffled Reactor (MAI-BR) - M. Zwain, Haider; Qamaruz Zaman, Nastaein; Abdul Aziz, Hamidi; Dahlan, Irvan (Current Environmental Engineering, 2014)
Research on lignin biodegradation is important in the field of global carbon cycling as well as in the bleaching and pulp industries. Therefore, a laboratory scale feasibility study on the anaerobic treatment of recycled paper mill effluent (RPME) in modified anaerobic inclining-baffled reactor (MAI-BR) was conducted for a period of 180 days. However, the removal of lignin was partially evaluated at the steady state condition of three different start-ups of MAIBR. The RPME is highly polluted and characterized by its lignin content which was found in the range of 40-50 mg/L. The lignin removal was found to be 40% and 53% for the 1st and 3rd start-up, respectively. Furthermore, the 2nd start-up did not achieve lignin removal due to the floatation of palm oil mill effluent (POME) seeding sludge during the early stage of MAI-BR start-up, respectively. Moreover, the lignin removal efficiencies increased down the reactor. Large part of lignin was removed in the first compartment. From the data of lignin removal efficiency, it was found that the reactor was operated quite well in a short start-up time.
Keywords: Lignin removal